2020
DOI: 10.1186/s12877-020-01530-x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in frailty among community-dwelling Chinese older adults and its predictors: evidence from a two-year longitudinal study

Abstract: Background: It is important to clarify the transitions and related factors of frailty for prevention of frailty. We evaluated the transitions of frailty among community-dwelling older adults and examined the predictors of the transitions. Methods: A cohort study was conducted among 3988 community residents aged ≥60 years during 2015 and 2017. A multiple deficits approach was used to construct the Frailty Index (FI) according to the methodology of FI construction, and sociodemographic characteristics and lifest… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 48 publications
4
27
0
1
Order By: Relevance
“…Frailty has been widely recognized as a geriatric syndrome and an emerging risk factor for adverse health outcomes in older adults. Frailty in older adults is linked to a greater risk of falls, hospitalization, disability, and death 1 , 2 . In Korea, reports indicate that the prevalence of frailty ranges from 2.5 to 31.7%, depending on the study sample and frailty scale measure 3 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Frailty has been widely recognized as a geriatric syndrome and an emerging risk factor for adverse health outcomes in older adults. Frailty in older adults is linked to a greater risk of falls, hospitalization, disability, and death 1 , 2 . In Korea, reports indicate that the prevalence of frailty ranges from 2.5 to 31.7%, depending on the study sample and frailty scale measure 3 5 .…”
Section: Introductionmentioning
confidence: 99%
“…In the study over 2 years of follow-up, it was reported that 6.9% older adults were aged 60 years and above [ 8 ]. In another study in Japan, it was reported that 7.2% older adults’ mean age was 73.0 [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported frailty transition rates based on their longitudinal research period [ 5 8 ]. However, the frailty transition rate might be different from the norm period since no one has ever experienced the impact of COVID-19 countermeasures earlier and thus, it cannot be predicted.…”
Section: Introductionmentioning
confidence: 99%
“…According to a review of previous research, the influencing factors of the undermet care needs of the disabled oldest old people were divided into the following categories in this study: (1) sociodemographic characteristics, including sex, age, education, marital status, place of residence and frailty index [ 46 , 53 , 54 , 55 , 56 ]. The frailty index was composed of eight parts, including the ADL, IADL (instrumental activities of daily living), objective physical performance, cognitive function, chronic disease, self-rated and interviewer-rated health, visual and hearing impairment, and number of times suffered from a serious illness in the past 2 years, which ranged from 0 to 1, with higher scores indicating weaker physical and mental functions of the oldest old people [ 57 , 58 ]. It should be pointed out that the Chinese version of MMSE (Mini-mental State Examination) is mainly used to measure the cognitive function of the older people, which is considered to be effective and applicable [ 6 , 12 ]; (2) family endowment, also called family resource, includes the human resources, economic resources, material resources, and social network resources which is the family actually or potentially owns.…”
Section: Methodsmentioning
confidence: 99%